Assessing the integration of peace and security into climate change policies in Southern Africa - Maphosa, Mandlenkosi; Synnestvedt, Thea; Gadu, Siyaxola; Campbell, Raramai; Maviza, Gracsious (2025)
Southern Africa is among the world’s most climate-vulnerable regions. The interrelated risks that climate impacts impose on food, land and water systems and the livelihoods of the people directly depending on them have been found to undermine social cohesion and increase human security risks across Southern Africa. In response, there is a need for governments in the region to acknowledge the specific risks that climate change and variability pose to their social systems and vulnerable populations and find suitable mechanisms to address the compounding risks of climate, peace and security. This paper aims to assess the extent to which climate, peace and security are provisioned for within existing climate-responsive policies in selected Southern African countries.